Hydraulic composition

By adding crystalline layered sodium silicate to a hydraulic composition of Portland cement and blast furnace slag, the initial strength is enhanced to match that of Portland cement alone, while preserving the mixture's flowability.

JP2025040806APending Publication Date: 2025-03-25TOKUYAMA CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023147839
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The replacement of blast furnace slag with a part of the cement in cement mixes results in a reduction of initial strength compared to using cement alone.

Method used

Incorporating crystalline layered sodium silicate into a hydraulic composition consisting of Portland cement and blast furnace slag, with a specific range of composition ratios, to enhance the initial strength and maintain flowability.

Benefits of technology

The addition of crystalline layered sodium silicate increases the initial strength of the hydraulic composition to be equivalent to or greater than that of Portland cement alone, while maintaining the flowability of the mixture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040806000001
    Figure 2025040806000001
  • Figure 2025040806000002
    Figure 2025040806000002
Patent Text Reader

Abstract

To provide a hydraulic composition that improves performance of blast furnace slag-containing cement to solve the problem that, being used as a cement admixture, a blast furnace slag has a low initial strength.SOLUTION: A hydraulic composition comprises Portland cement, a blast furnace slag, and a crystalline layered sodium silicate, wherein: the Portland cement is 70 pts.mass or more and less than 95 pts.mass; the blast furnace slag is more than 5 pts.mass and 30 pts.mass or less (provided that the total of the Portland cement and the blast furnace slag is 100 pts.mass); and the crystalline layered sodium silicate is 2 mass% or more and 12 mass% or less of the total composition whereby even if the blast furnace slag is partially replaced with cement, an initial strength is equivalent to or more than that of cement alone.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydraulic composition comprising Portland cement, blast furnace slag and crystalline layered sodium silicate. More specifically, the present invention relates to a hydraulic composition containing blast furnace slag that improves early strength development. More specifically, the present invention relates to a hydraulic composition containing blast furnace slag that improves early strength development by utilizing crystalline layered sodium silicate in the hydraulic composition. [Background technology]

[0002] In relation to recent global environmental problems, the effective use of waste, by-products, etc. has become an important issue. Taking advantage of the characteristics of the cement industry and cement manufacturing facilities, the effective use or treatment of waste as raw materials or fuel during cement manufacturing is considered effective from the viewpoint of safety and large-scale disposal.

[0003] The cement industry is a mass production and mass consumption industry, and it is considered important for it to effectively use or process waste materials as raw materials or fuels during cement production, and to produce cement efficiently while conserving resources and energy.

[0004] On the other hand, from the perspective of global warming, the cement industry is considered to be an industry with high CO2 emissions. CO2 emitted in the cement industry is due to the decarbonation of limestone, which is a raw material for clinker, during the cement manufacturing stage. Blended cement with a reduced amount of clinker is considered effective in reducing CO2 emissions in the cement industry. One of the components of such blended cement is blast furnace cement, which contains blast furnace slag. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Takeshi Iyoda: Concrete using large amounts of ground granulated blast furnace slag, Concrete Engineering, Vol. 52, No. 5, pp. 409-414 (2014) [Non-Patent Document 2] Atsushi Tanidagai et al.: Properties of Blast-furnace Cement Type A using clinker with adjusted mineral composition, Proceedings of the Cement and Concrete Society, Vol. 66, pp. 338-345 (2012) Summary of the Invention [Problem to be solved by the invention]

[0006] However, when blast furnace slag is used as a cement admixture to replace part of cement, there is a problem that the initial strength is lower than when cement is used alone (Non-Patent Documents 1 and 2). Therefore, the present invention provides a hydraulic composition which, even when using a cement containing blast furnace slag, exhibits early strength development equal to or greater than that of general-purpose cement. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems, and have found that crystalline layered sodium silicate acts as a stimulant to bring out the latent hydraulic properties of blast furnace slag.

[0008] As a result, they discovered that the Na2O contained in crystalline layered sodium silicate increases the latent hydraulic properties of blast furnace slag, and that SiO2 reacts with cement to form hydrates, thereby increasing the early strength, which led to the completion of the present invention.

[0009] Applications of hydraulic compositions include mortar, ready-mix concrete, and secondary factory products. When water glass or powdered sodium silicate (sodium silicate), which are generally known as quick-setting additives, is added to ready-mix concrete, the alkali concentration rises rapidly, causing a quick-setting effect, which leads to a problem of significantly deteriorating workability in terms of fluidity, viscosity, etc. However, it has been discovered that crystalline layered sodium silicate can ensure fluidity in addition to improving early strength development because the alkali concentration rises slowly when dissolved.

[0010] That is, the present invention is a hydraulic composition comprising Portland cement, blast furnace slag and crystalline layered sodium silicate, the Portland cement being at least 70 parts by mass but less than 953 parts by mass, the blast furnace slag being more than 5 parts by mass but not more than 30 parts by mass (wherein the sum of the Portland cement and the blast furnace slag is taken as 100 parts by mass), and the crystalline layered sodium silicate being at least 2% by mass but not more than 12% by mass of the total composition.

[0011] In the hydraulic composition, the crystalline layered sodium silicate is represented by the following formula (1): Na x H (2-x) ySi2O5 zH2O (1) (In the formula, x is a number greater than 0 and equal to or less than 2, y is a number equal to or less than 1±0.1, and z is a number greater than 0 and equal to or less than 5.) It is preferable that the composition of the compound is as follows: Effect of the Invention

[0012] According to the present invention, the hydraulic composition of the present invention can obtain early strength equal to or greater than that obtained when Portland cement is used alone, without decreasing fluidity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The hydraulic composition of the present invention is composed of Portland cement, blast furnace slag, and crystalline layered sodium silicate, and contains 70 parts by mass or more and less than 95 parts by mass of the Portland cement, more than 5 parts by mass and less than 30 parts by mass of the blast furnace slag (wherein the total of Portland cement and blast furnace slag is 100 parts by mass), and contains 2% by mass or more and 12% by mass or less of the crystalline layered sodium silicate based on the total composition. As described above, when blast furnace slag is substituted for a part of the cement, the initial strength is lowered compared to when the cement is used alone. Therefore, in the present invention, crystalline layered sodium silicate is added to eliminate this effect.

[0014] The Portland cement used in the present invention is a known Portland cement as specified by the JIS standard. Specifically, it is one that satisfies JIS R 5210 "Portland cement", and includes various types of Portland cement such as normal, early strength, super early strength, medium heat, low heat, and sulfate resistant.

[0015] The blast furnace slag used in the present invention may be any blast furnace slag known as a cement admixture. Specifically, any blast furnace slag produced as a by-product in steelworks may be crushed and used without any restrictions. The fineness of the blast furnace slag may be within the range of general use, and may be in the range of 3000 to 8000 cm. 2 It is preferable that the molecular weight is adjusted to 1 / g.

[0016] In the present invention, the amount of Portland cement and blast furnace slag cement used is 70 parts by mass or more and less than 95 parts by mass, and the amount of blast furnace slag used is more than 5 parts by mass and not more than 30 parts by mass, assuming that the total amount of Portland cement and blast furnace slag is 100 parts by mass. When Portland cement contains blast furnace slag as a minor mixed component as specified in 5.3 (minor mixed components) of JIS R 5210, the amount of this blast furnace slag is included in the amount of the blast furnace slag.

[0017] If the amount of blast furnace slag mixed exceeds 30 parts by mass, it becomes difficult to obtain the same early strength as when cement is used alone.

[0018] Instead of using Portland cement and blast furnace slag individually, a mixed cement consisting of Portland cement and blast furnace slag may be used. As the mixed cement consisting of Portland cement and blast furnace slag, the well-known blast furnace cement type A specified in JIS R 5211 can be used.

[0019] In the present invention, the total composition contains 2% by mass or more and 12% by mass or less of crystalline layered sodium silicate.

[0020] When using common sodium silicates such as water glass and powdered sodium silicate, they are non-crystalline and have a relatively high solubility in water, and when used in ready-mix concrete, for example, they significantly increase the alkali concentration in the ready-mix concrete and reduce its fluidity. In addition, they react rapidly with cement to gel, which also significantly reduces the fluidity and greatly affects workability.

[0021] If the amount of crystalline layered sodium silicate added is less than 2% by mass, the effect of increasing early strength is not sufficiently obtained. If the amount exceeds 12% by mass, the effect of increasing early strength is obtained, but the amount of alkali increases, making it difficult to obtain the required fluidity and deteriorating workability.

[0022] The crystalline layered sodium silicate is a sodium silicate which exhibits an orthorhombic or monoclinic crystal structure and has a layered structure.

[0023] Such crystalline layered sodium silicate is specifically Na2Si 22 O 45 Kenyaite, Na2Si, represented by xH2O 14 O 29 Magadiite, represented by xH2O, Na2Si8O 17 Examples include those with the formula Na2Si2O5, etc.

[0024] Among these, the following formula (1) is preferred because the increase in alkali concentration during dissolution is gradual. Na x H (2-x) ySi2O5 zH2O (1) (In the formula, x is a number greater than 0 and equal to or less than 2, y is a number equal to or less than 1±0.1, and z is a number greater than 0 and equal to or less than 5.) The crystalline layered sodium silicate represented by the following formula is preferably used.

[0025] The crystalline layered sodium silicate represented by formula (1) may contain metal elements such as Na, K, Mg, Ca, and Al, as long as the effects of the present invention are not adversely affected. The amount of these elements mixed in is preferably 0.005 mol or less per mol of Na.

[0026] Crystalline layered sodium silicate shown in formula (1) dissolves after reacting with water and changing its crystal phase to kanemite (NaHSi2O5·3H2O). Therefore, it takes time for it to dissolve, and it is presumed that the increase in alkali concentration is gradual.

[0027] The crystalline layered sodium silicate represented by formula (1) is commercially available, and specific examples thereof include "Purifeed" (Na2Si2O5) manufactured by Tokuyama Corp. The crystalline layered sodium silicate exists in the form of powder or granules, and its particle size is 10 to 100 μm, preferably 30 to 80 μm.

[0028] The hydraulic composition of the present invention can be produced by mixing each of the components, Portland cement, blast furnace slag, and crystalline layered sodium silicate. There is no particular restriction on the order of mixing each of the components. A preferred method for producing the hydraulic composition of the present invention includes a method in which Portland cement, blast furnace slag, and crystalline layered sodium silicate are mixed at the same time in a lump. The hydraulic composition of the present invention may be prepared by mixing each of the components in advance to prepare a hydraulic composition, which may be used as necessary, or may be prepared by mixing each of the components at the time of use to prepare a hydraulic composition, which may be used. For example, when mixing at the time of use, a mixer used for kneading paste, mortar, and ready-mixed concrete can be used without restriction as a mixer, and specifically, a pan mixer, a forced twin-shaft mixer, etc. can be used. As described above, a mixed cement consisting of Portland cement and blast furnace slag may be used as the Portland cement and blast furnace slag.

[0029] The hydraulic composition of the present invention can be used in the same manner as Portland cement. Specifically, it is used in the form of paste, mortar, and concrete, and the water-powder ratio of the hydraulic composition to water is not particularly limited as long as it is within the range generally used, and is usually 25% to 70%. When it is used in the form of mortar or concrete, fine aggregates and coarse aggregates generally used in the manufacture of mortar and concrete, that is, river sand, land sand, crushed sand, river gravel, mountain gravel, crushed stone, etc., can be used. In addition, known admixtures such as AE water reducing agents, high-performance water reducing agents, high-performance AE water reducing agents, and air content adjusters may be used within the range not impairing the effects of the present invention. EXAMPLES

[0030] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Furthermore, not all of the combinations of features described in the examples are necessarily essential to the solution of the present invention.

[0031] (1) Combination The blend ratio is shown in Table 1. A hydraulic composition of the present invention was prepared by blending cement, blast furnace slag, and crystalline layered sodium silicate in the ratios shown in Table 1. In this example, in order to evaluate the hydraulic composition, water, fine aggregate, and coarse aggregate were blended with the prepared hydraulic composition to prepare concrete.

[0032] The water used was tap water. The cement used was ordinary Portland cement (density 3.16 g / cm) conforming to JIS R 5210 (Portland cement). 3 , powder degree 3270cm 2 The blast furnace slag used was one with a density of 2.91 g / cm3, which complies with JIS A 6206 (ground blast furnace slag for concrete). 3 , powder degree 4000cm 2 The fine aggregate used was crushed sand (density 2.64 g / cm3) conforming to JIS A 5005 (crushed stone and crushed sand for concrete). 3 ) and dune sand (density 2.58 g / cm 3) mixed sand was used, and the coarse aggregate was hard sandstone crushed stone (maximum size 20 mm, density 2.70 g / cm3) conforming to JIS A 5005 (crushed stone and crushed sand for concrete). 3 The crystalline layered sodium silicate used was crystalline layered sodium silicate having a chemical composition represented by Na2Si2O5 (Tokuyama Corporation's "Purifeed", density 2.43 g / cm 3 For comparison, powdered sodium silicate (density 2.50 g / cm3) with the same SiO2 / Na2O molar ratio as the crystalline layered sodium silicate was used. 3 , abbreviation: PS) was used.

[0033] The increase in volume due to the mixing of blast furnace slag, crystalline layered sodium silicate, and powdered sodium silicate was adjusted by reducing the amount of fine aggregate.

[0034] <Reference example> It does not contain blast furnace slag or sodium silicate, only ordinary Portland cement.

[0035] <Comparative Examples 1 and 2> Blast furnace slag was added in amounts of 10 and 20 parts by mass per 100 parts by mass of cement and blast furnace slag combined.

[0036] <Comparative Example 3, Examples 1 and 2> Blast furnace slag was added in an amount of 10 parts by mass per 100 parts by mass of the total of cement and blast furnace slag, and crystalline layered sodium silicate was added in an amount of 1, 3, or 10% by mass per 100% by mass of the hydraulic composition.

[0037] <Examples 3 to 5, Comparative Example 4> Blast furnace slag was added in an amount of 20 parts by mass based on a total of 100 parts by mass of cement and blast furnace slag, and crystalline layered sodium silicate was added in an amount of 3, 5, 10, or 20% by mass based on 100% by mass of the hydraulic composition.

[0038] <Comparative Example 5> Blast furnace slag was added in an amount of 20 parts by mass based on a total of 100 parts by mass of cement and blast furnace slag, and powdered sodium silicate was added in an amount of 3 and 1% by mass based on 100% by mass of the hydraulic composition.

[0039] [Table 1]

[0040] *1 Water powder ratio (%) = (water (kg) / hydraulic composition (kg)) × 100 *2 Blast furnace slag (parts by mass) = (blast furnace slag (kg) / [cement (kg) + blast furnace slag (kg)]) x 100 *3 Sodium silicate (%) = (Sodium silicate (kg) / Hydraulic composition (kg)) x 100

[0041] (2) Slump measurement The slump immediately after mixing was measured in accordance with JIS A 1101:2020 "Concrete slump test method." The standard is 18.0±1.5cm, and a large slump indicates high fluidity, while a small slump indicates reduced fluidity. This is a physical property value that serves as an indicator of workability. The results are shown in Table 2.

[0042] (3) Measurement of daily intensity The compressive strength of the concrete was measured at one day of age in accordance with JIS A 1108:2018 "Method of testing compressive strength of concrete". The size of the specimen was Φ100×200mm. The results are shown in Table 2.

[0043] [Table 2]

[0044] Comparative Examples 1 and 2 show a tendency for the addition of blast furnace slag to decrease the one-day strength.

[0045] In Comparative Example 3, the one-day strength was lower than that of the Reference Example, and it is understood that when the amount of crystalline layered sodium silicate added is small, the effect of increasing the initial strength cannot be obtained.

[0046] Examples 1 to 5 show one-day strength values ​​equal to or higher than those of Reference Examples. Also, the slump values ​​are within a predetermined range, and it is understood that the hydraulic composition of the present invention, which contains crystalline layered sodium silicate in an amount of 2% by mass to 12% by mass in the total composition, can achieve the effect of increasing early strength without decreasing fluidity.

[0047] In Comparative Example 4, the amount of crystalline layered sodium silicate added was large, which reduced the fluidity and made mixing difficult, making it impossible to evaluate.

[0048] In Comparative Example 5, the one-day strength exceeded that of the Reference Example, but the specified slump value was not achieved, and it is clear that when general sodium silicate (sodium silicate powder) is used instead of crystalline layered sodium silicate, the fluidity decreases and the workability deteriorates.

[0049] In Comparative Example 6, even though the amount of sodium silicate powder added was 1% in order to improve the fluidity, the fluidity was not equal to that of the Reference Example, and furthermore, the strength was lower than that of the Reference Example.

Claims

1. A hydraulic composition comprising Portland cement, blast furnace slag and crystalline layered sodium silicate, the Portland cement being 70 parts by mass or more and less than 95 parts by mass, the blast furnace slag being more than 5 parts by mass and 30 parts by mass or less (wherein the total of the Portland cement and the blast furnace slag is 100 parts by mass), and the crystalline layered sodium silicate being 2% by mass or more and 12% by mass or less of the total composition.

2. The crystalline layered sodium silicate is represented by the following formula (1): Yes x H (2-x) Yes 2 Oh 5 ・zH 2 O (1) (In the formula, x is a number greater than 0 and equal to or less than 2, y is a number equal to or less than 1±0.1, and z is a number greater than 0 and equal to or less than 5.) 2. The hydraulic composition according to claim 1, having a chemical composition represented by the formula: